MAʾNĀ ALFĀZ SŪRAH LUQMAN (DIRĀSAH TAHLĪLIYYAH DILĀLIYYAH) - pita sari (Jurnal Al-Maqoyis, 2020)
The discussion of meaning takes a very important role in language learning. From there we can see how important it is to study Semantics. This article aims to understand: 1) Types of meanings in the verses of Holy Qur’an Surah Luqman, 2) The relation between the verse words of Surah Luqman and their meanings contained in the book At-Tahrir wa Tanwir. This research is a literature study, using a qualitative approach, the data analysis technique used in this research is content analysis. The primary data in this research are the verses of Surah Luqman and their meanings contained in the book At-Tahrir wa Tanwir, and the secondary data in this research were taken from books related to the research. The result of this research is, researchers found 10 types of meanings in the verses of Surah Luqman which rever to the meanings contained in the book At-Tahrir wa Tanwir, namely: Lexical Meaning, Contextual Meaning (language context), Functional Meaning of Syntatic Structure, Functional Meaning of Morphological Structure,Word Meaning, Referential Meaning, Stylistic Meaning, Conceptual Meaning, Figurative Meaning, Meaning of Terms. And the relation between the verse words and its meaning occurs in 3 types of relations, namely: Synonim, Polysemy, Hypernym and Hyponym. Keywords: Types of Meaning, Relations of Meanings, Surah Luqman, Tafsir At-Tahrir wa Tanwir, Ibnu ‘Asyur,  Semantic Analysis